Second-generation antipsychotics and metabolic syndrome: a role for mitochondria - Mortimer, Katherine R. H.; Katshu, Mohammed Zia Ul Haq; Chakrabarti, Lisa (Frontiers in Psychiatry, 2023)
Psychosis is a known risk factor for developing metabolic syndrome (MetS). The risk is even greater in patients who are taking second-generation antipsychotics (SGAs). SGAs exacerbate metabolic abnormalities and lead to a 3-fold increased risk of severe weight gain, type 2 diabetes, and cardiovascular disease in patients. Mitochondrial dysfunction is a hallmark of MetS. Mitochondria process glucose and fatty acids into ATP. If these processes are impaired, it can result in dyslipidaemia, hyperglycaemia and an imbalance between nutrient input and energy output. This leads to increased adiposity, insulin resistance and atherosclerosis. It is unclear how SGAs induce MetS and how mitochondria might be involved in this process. It has been found that SGAs impair cellular glucose uptake in liver, dysregulating glucose and fatty acid metabolism which leads to an accumulation of glucose and/or lipids and an increase reactive oxygen species (ROS) which target mitochondrial proteins. This affects complexes of the electron transport chain (ETC) to reduce mitochondrial respiration. While there is a suggestion that SGAs may interact with a variety of processes that disrupt mitochondrial function, some of the results are conflicting, and a clear picture of how SGAs interact with mitochondria in different cell types has not yet emerged. Here, we outline the current evidence showing how SGAs may trigger mitochondrial dysfunction and lead to the development of MetS.